2012
DOI: 10.1119/1.4751875
|View full text |Cite
|
Sign up to set email alerts
|

Confined modes in two-dimensional tubes

Abstract: On the Aharonov-Casher system and the Landau-Aharonov-Casher system confined to a two-dimensional quantum ring J. Math. Phys. 53, 023514 (2012) We survey various numerical methods for finding solutions of quantum confined states. We especially consider states in two-dimensional (2D) tubes, or 2D surfaces that are confined in the transverse direction but are unconfined in the longitudinal direction. We first review existence proofs for bound states in long 2-D tubes. We then review various methods for finding s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The effect of bound states in infinite non-straight waveguides has been studied in [7,8,9,10,11,12]. It is worth mentioning a recent pedagogical article by Londergan and Murdock [13], that illustrates different numerical methods for the solutions of confined systems, in particular two-dimensional waveguides.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of bound states in infinite non-straight waveguides has been studied in [7,8,9,10,11,12]. It is worth mentioning a recent pedagogical article by Londergan and Murdock [13], that illustrates different numerical methods for the solutions of confined systems, in particular two-dimensional waveguides.…”
Section: Introductionmentioning
confidence: 99%
“…Such realizations are indeed susceptible of manipulations that produce partial isospectrality: we should bear in mind that the Dirichlet boundary value problem posed by bent waveguides leads to non-trivial behavior at high energies or frequencies, connecting the problem with wave-like manifestations of chaos [26]. However, at very low energies we can take advantage of trapped states at corners [14,[27][28][29][30] (in fact, only one bound state at a right bending angle), providing an exponentially evanescent coupling of two corners as a function of the distance between them. The idea then is to accommodate as many levels as necessary below the propagation threshold of the guide; this is done by adjusting the distances between the corners contained in the array; see figures 1, 6 and 7.…”
Section: Bent Waveguide Realizationsmentioning
confidence: 99%
“…At low temperature and small electric bias, only the electrons near the Fermi energy contribute to the current. It has been shown that, under certain conditions, the propagation of ballistic electrons in semiconductor quantum wires, of electromagnetic waves in wave guides, of sound waves in pipes with different geometry, light propagation in optical fibres for photonic applications are all described by the same type of Helmholtz equation [9][10][11][12][13]. For the same boundary conditions this equation generates the same eigenvalue problem with the same solution.…”
Section: Introductionmentioning
confidence: 99%